Service-Learning as the Violence of Mercy after the 2010 Haitian Earthquake - Bailey, Megan Snider (Engaged Scholar Journal, 2023)
This article draws on Paul Farmer’s ideas of accompaniment (2011) and “expert mercy” (2020, para. 2) and La Paperson’s (2010) notion of the “violence of mercy” (p. 25) to demonstrate how the short-term, outsider service-learning response to the 2010 Haitian earthquake does not benefit community-identified needs. This is done by investigating the best practices of the Haiti Compact, a cohort of U.S. colleges and universities and an alternative break nonprofit operating short-term, outsider service-learning initiatives in post-earthquake Haiti in thoughtful ways intending to help with the recovery efforts while meaningfully contributing service via the routine presence of international volunteers. Despite good intentions, their material practices of service-learning risk harm for community partners and fail to meet established best practice goals. By examining the work of service-learning educators who commit to best practices, we can understand the limits of possibility for the pedagogy and point to alternatives that offer merciful responses to communities in crisis.